Synthesis and Characterization of Lithium Iron Phosphate Carbon Composite (LFP/C) using Magnetite Sand Fe3O4 - Zuffa Anisa; Mochammad Zainuri (Chemistry Department, The University of Brawijaya, 2020)
Lithium Ferro Phosphate Carbon Composite (LFP/C) had been synthesized using solid-state reaction method. Magnetite sand Fe3O4 was used as Fe- source in LFP/C synthesized. Calcination temperature of the sample performed at 400, 500, and 600°C. The phase and composition of samples determined by Rietveld analysis of X-ray diffraction (XRD) pattern. The dominant identified phase at 400°C was diphosphate LiFeP2O7, and the others phases were nasicon Li3Fe2(PO4)3 and hematite Fe2O3. As the temperature getting higher the diphosphate phase LiFeP2O7 transform to nasicon Li3Fe2(PO4)3.The chemical bonds, lattice vibration and other structural features of the sample were investigated using FTIR spectroscopy in range of 1400 – 400 cm-1. Specific vibration modes in LFP-1 to LFP-3 for each bonding were shown by the high intense in certain wavenumber.